Identification of short single disulfide-containing contryphans from the venom of cone snails using de novo mass spectrometry-based sequencing methods. (15th June 2017) - Franklin, Jayaseelan Benjamin; Rajesh, Rajaian Pushpabai; Vinithkumar, Nambali Valsalan; Kirubagaran, Ramalingam
Abstract: We identified 12 short single disulfide-containing conopeptides from the venom of Conus coronatus, C. leopardus, C. lividus and C. zonatus . Interestingly, we detected the shortest contryphan sequence thus far characterized which contains only six amino acid residues. We also identified three distinct contryphan sequences of C. lividus without any proline residues and one sequence with an unusual post-translational modification (bromination of tryptophan). Furthermore, we characterized venom peptides of C. zonatus for the first time. Graphical abstract: Highlights: Identified short contryphan sequences with six amino acid residues. Novel report of three contryphan sequences lacking proline. An unusual post-translational bromination of tryptophan detected in contryphan. Initial report on venom peptides of Conus zonatus.